ApoC-III gene polymorphisms and risk of coronary artery disease - Oliviero Olivieri; Chiara Stranieri; Antonella Bassi; Barbara Zaia; Domenico Girelli; Francesca Pizzolo; Elisabetta Trabetti; Suzanne Cheng; Michael A. Grow; Pier Franco Pignatti; Roberto Corrocher (Journal of Lipid Research, 2002)
Several polymorphisms in the apolipoprotein C-III (apoC-III) gene have been associated with hypertriglyceridemia, but the link with coronary artery disease risk is still controversial. In particular, apoC-III promoter sequence variants in the insulin responsive element (IRE), constitutively resistant to downregulation by insulin, have never been investigated in this connection. We studied a total of 800 patients, 549 of whom had angiographically documented coronary atherosclerosis, whereas 251 had normal coronary arteriograms. We measured plasma lipids, insulin, apoA-I, apoB, and apoC-III and assessed three polymorphisms in the apoC-III gene, namely, T-455C in the IRE promoter region, C1100T in exon 3, and Sst1 polymorphic site (S1/S2) in the 3′ untranslated region. Each variant influenced triglyceride levels, but only the T-455C (in homozygosity) and S2 alleles influenced apoC-III levels. In coronary artery disease (CAD) patients, 18.6% were homozygous for the −455C variant compared with only 9.2% in CAD-free group (P < 0.001).In logistic regression models, homozygosity for −455C variant was associated with a significantly increased risk of CAD (OR = 2.5 and 2.18 for unadjusted and adjusted models, respectively) suggesting that it represents an independent genetic susceptibility factor for CAD.